Transversus Abdominis Thickness at Rest and Exercise in Individuals with Poststroke Hemiparesis - Anna Kelli; Eleftherios Kellis; Nikiforos Galanis; Konstantinos Dafkou; Chrysostomos Sahinis; Athanasios Ellinoudis (MDPI AG, 2020)
The activity of the transverse abdominal (TrA) muscle affects the stabilization of the trunk. It is known that after a stroke, people experience problems in performing daily activities. The purpose of this study was to examine whether there are differences in the transversus abdominal thickness between the two sides of the body in individuals with hemiparesis and controls. Eight patients with hemiparesis and nine controls matched for age and body mass index were examined by musculoskeletal ultrasound in four conditions: a) At rest, b) abdominal hollowing maneuver from the supine position, c) bridge, and d) abdominal hollowing maneuver from the bridge position. In each of the above conditions, the symmetry index was calculated as the absolute value of the difference in thickness between the two sides. Analysis of variance showed a lower TrA thickness at rest and exercise in patients compared to the control group (p < 0.05). Further, patients showed a lower contraction thickness ratio during exercise compared to controls (p < 0.05). The absolute symmetry of the TrA thickness was 12.59 ± 6.43% to 19.31 ± 10.43% in patients and it was significantly greater than the control group (3.01 ± 2.47% to 4.47 ± 2.87%). According to the above results, it seems that transverse abdominal activation exercises are particularly useful for improving the stability of patients with hemiparesis, as long as they are located and adapted to the deficit of each patient.